Digital Creativity: A Survey for the Project Invisibilia - Pizzo, Antonio; Valle, Andrea (Mimesis Journal, 2014)
The paper presents one of the task of project Invisibilia Project and confirms that the term “digital creativity” represents a disperse notion in which a number of different definition developed along last decades are merged. The dispersion of the concept emerge from the bibliometric analysis that has used a set of seminal essays and articles and has created a citation database. Nevertheless the analysis reveals that the discussion about the notion is still gemmed out of a core of pivotal figures in the field of structuralism, mass-mediology and new media. This seems to lead to the conclusion that the digital creativity as a field is less influenced by computer science scholars and still lack of a specific canon.